Assessment of Soil Degradation under Different Land Uses and Conservation-Based Management in Banjar Subdistrict, Buleleng Regency - Made Sri Sumarniasih; Cindy Anita Sitanggang; I Wayan Narka (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2026)
Land-use change and agricultural intensification in Banjar Subdistrict have the potential to degrade soil quality and disrupt biomass production. This study aimed to assess the potential, spatial distribution, and status of soil degradation under different land uses and to formulate conservation-based management strategies. The methods included field surveys, laboratory analyses, and spatial analysis using Geographic Information Systems (GIS) through overlay techniques of land use, soil type, slope, and rainfall maps. Soil samples were collected from 13 Homogeneous Land Units (HLUs) representing different land-use types and biophysical conditions. The results showed that moderate soil degradation potential dominated an area of 9,801.46 ha (85.55%), followed by high potential on steep slopes covering 1,026.02 ha (8.95%) and low potential in lowland areas covering 629.96 ha (5.50%). The soil degradation status was classified as light and distributed into three spatial units (R.I-p; R.I-p,f,a; R.I-p,v,a), with permeability, soil fraction, porosity, and pH as the main limiting factors. Recommended management practices include terracing, runoff control, cover cropping, organic matter application, crop rotation, and balanced fertilization.